Value Approach and Character Education in Reviewing Cohabitation Phenomenon - Ni Luh Gede Yogi Arthani (Fakultas Hukum, Universitas Warmadewa, 2019)
Coexistence between two people who have a love affair without marriage ties is called cohabitation, or what is in Indonesian language termed